Nanoflower hydroxyapatite's effect on the properties of resin-based dental composite - Sagir, Kadir; Aydinoglu, Aysu; Yoruc, Afife Binnaz Hazar (WILEY, 2024)
To investigate the reinforcing effect of nanoflower-like hydroxyapatite (NFHA) in resin-based dental composites, we synthesized a novel NFHA using microwave irradiation (MW), hydrothermal treatment (HT), and sonochemical synthesis (SS). Silanized NFHA was then used as the reinforcing filler in dental resin composites. We characterized the structure and morphology of various HA nanostructures using x-ray diffraction, scanning electron microscope, and TEM. The mechanical performance of dental resin composites reinforced with silanized NFHA was measured using a universal testing machine. Spherical HA, synthesized through chemical precipitation (CP), served as the control group. One-way analysis of variance was employed for the statistical analysis of the acquired data. The results demonstrate that the nanoflower morphology significantly was improved mechanical and physical properties. After conducting trials, the NFHA synthesized using MW and HT showed a substantial enhancement in mechanical and physical properties compared to the other structures. Therefore, it can be concluded that NFHA can serve as a novel reinforcing HA filler, providing regenerative properties to resin composites with sufficient mechanical strength. Synthesis of hydroxyapatite nanoflowers for reinforced resin-based dental composites with improved mechanical properties and natural tooth color matching. image
Keywords: bioengineering; biomaterials; nanocrystals; nanoparticles; nanowires; resins; Polymer Science